MODERN TENDENCIES IN AMERICAN SHORT STORY GENRE - Mirmuhsin Yuldashev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article surveys a writing style of modern American writers. It is inevitable that American literature is considered to be one of the most important part of the world lit1erature, it brought many masterpieces by talented and outstanding authors. Each period of it is rich in great writers and their works which reflected the life of the nation of time.